Participatory Legal Empowerment in Religious Asset Disputes: The Muhammadiyah Singosari Case - Fajrin, Yaris Adhial; Kurniawan, Kukuh Dwi; Iradhad Taqwa Sihidi; Agustino, Hutri (Indonesian Journal of Legal Community Engagement, 2025)
Land disputes involving religious organizations often pose significant challenges, especially when historical documentation is fragmented or incomplete. This study focuses on a land ownership conflict between a private individual and the Muhammadiyah organization in Singosari District, Malang Regency. The main objective of this research is to assist Muhammadiyah in resolving a property dispute concerning land utilized for educational purposes, namely the Aisyiyah Bustanul Athfal 3 Kindergarten. Using a Participatory Action Research (PAR) approach, the research involved initial legal consultations, document verification, stakeholder interviews, direct field observations, and multiple rounds of coordination with both local and central leadership of Muhammadiyah. The findings show that both parties hold different legal claims: one based on an old eigendom verponding title from 1948 and the other on a recently issued land certificate (SHM) in 2023. Despite these conflicting claims, negotiation and mediation were identified as the preferred methods due to the parties' shared institutional history. The study concludes that while the resolution process is still ongoing, the PAR method facilitated a structured, inclusive, and empathetic approach. It is recommended that similar conflicts within religious or social institutions adopt early legal counseling and structured non-litigation pathways to avoid costly and prolonged litigation. Future community service programs should focus on strengthening legal awareness and improving asset documentation practices within civil society organizations